Nutrient Composition of Selected Cooked and Processed Snack Foods - Tee, E Siong; Shahid, Siti Mizura; Ariffin, Anuar; Kuladevan, R.; Young, S. I.; Khor, Swan Choo; Chin, S. K. (1989)
Nutrient composition of 27 cooked snack foods and 19 processed snacks was determined. The cooked foods were mostly cereal based, made from wheat flour, rice or rice flour, and almost all of them were traditional Malaysian kuih or dishes. The processed snacks studied were chocolate, cereal, tuber, fish and prawn products. The levels of 19 nutrients were tabulated, expressed as per 100 g edible portion. Selected nutrients in each serving or packet of the foods were also presented. The paper is intended as a contribution to the knowledge on nutrient composition of local snack foods, for which information is still greatly lacking. The number of foods studied is only a fraction of the total number available. More work in this area will have to be carried out, to meet the increasing demand for such data.